Synthesis of hazard-free customized CMOS complex-gate networks under multiple-input changes - Kudva, P.; Gopalakrishnan, G.; Jacobson, H.; Nowick, S.M. (33rd Design Automation Conference Proceedings, 1996, 1996)
This paper addresses the problem of realizing hazard-free single-output Boolean functions through a network of customized complex CMOS gates tailored to a given asynchronous controller specification. A customized CMOS gate network can either be a single CMOS gate or a multilevel network of CMOS gates. It is shown that hazard-free requirements for such networks are less restrictive than for simple gate networks. Analysis and efficient synthesis methods to generate such networks under a multiple-input change assumption (MIC) are presented.